HEAT EXPOSURE ANALYSIS ON WORKERS OF PARKING LOT BUILDING FOR SHOPPING CENTER X - Nandywardhana, Fidelis
Parking building is an essential parts for a shopping mall building in a big cities in Indonesia, such as Bandung, because of the dependency of using personal transportation than the public transportation. Types of parking space and vehicle density affect heat exposure in the parking building. Heat exposure from working environment can lead to worker's health problem. The heat exposure measured by Wet Bulb Globe Temperature (WBGT), Heat Stress Index (HSI), Predicted Mean Vote (PMV), and Predicted Percentage of Dissatisfied (PPD). Potential health effects from the heat exposure can be showed by the changes of the worker’s heart rate and blood pressure after work. All of the WBGT measurements are not exceeding the TLV based on Indonesian Kepmenaker No. 51/1999, which is 30oC. The maximum ISBB measurement is 28oC in basement 1st floor. The activity and the vehicle crowdedness are the main factor to the increase of heat exposure to workers in the parking building. The heat exposure effects to the workers are the increase of heart rate and the decrease of blood pressure. The blood vessel will expand and the blood pressure will be decreased and the heart rate will increase to stabilize the body. Another physiological effect that occurred is dehydration that can lead to fatigue and drowsiness. The PMV shown that the highest heat sensation to the workers are in basement 1st floor at around range +2 (warm) with unsatisfied level at 70%. The average energy that the workers consumed for work is 0.34 kkal/minutes. The average consumed energy is still below the consumed energy standard, so that means the break time for 30-45 minutes is already sufficient enough for the workload and the workplace conditions. The break time extension is not needed based on the facts. The general ventilation system’s improvement is required for the improvement of thermal comfort.